PELAKSANAAN PERJANJIAN PRANIKAH DIHUBUNGKAN DENGAN PEMBAGIAN HARTA BERSAMA PASCA PERCERAIAN DI PENGADILAN AGAMA PEKANBARU - SYAHRIAL HUKUM (Pahlawan Tuanku Tambusai University, 2021)
Abstract Prenuptial agreement is an agreement made before the marriage. This agreement contains the problem of the division of property between the two brides so that it can be separated in case of divorce or death. A prenuptial agreement that has been ratified by a marriage registrar is binding and applies as a law for prospective spouses and third parties, if the prenuptial agreement that has been made by the husband and wife has not been implemented or there is a violation of the agreement that has been made, then it automatically gives the right to the wife to ask for marriage termination or as a reason for divorce. Therefore, legal protection for joint property after divorce in a prenuptial agreement is that if during the marriage the husband violates the contents of the prenuptial agreement, the wife can file for divorce in the Religious Court (Article 51 Compilation of Islamic Law) while other legal protections in the prenuptial agreement may regarding â€œtaklik talakâ€, Article 46 Compilation of Islamic Law, namely the husband's promise to divorce his wife in certain circumstances such as the husband leaves his wife or does not obey his obligations. A wife has the right to file a divorce claim based on the violation of â€œtaklik talakâ€ while the joint property is the property obtained during the marriage. Whereas those who entered into a prenuptial agreement in 2016 were 3 couples and the most frequent obstacles in a prenuptial agreement include husband and wife in bad faith in the case of debts owed to third parties, prospective husband or wife violating the contents of the marriage agreement, during the marriage of the husband or the wife violates the contents of the marriage agreement and there is a civil dispute regarding the contents of the marriage agreement. Keywords : Agreement, Premarital, Shared Wealth